A Three-Tier Chemotherapy Response Score For Ovarian/Fallopian Tube/Peritoneal High Grade Serous Carcinoma, Is It Clinically Relevant? - Lawson, Barrett C. (Am J Surg Pathol, 2020)
The chemotherapy response score (CRS) is used to score histopathologic response to neoadjuvant chemotherapy (NACT) of patients with extrauterine high grade serous carcinoma. This study was undertaken to determine if the CRS in the omentum, adnexa or when combined correlates with 1) progression free survival (PFS) or overall survival (OS), 2) laparoscopic score of abdominal disease, 3) CA-125 levels, 4) BRCA status and 5) platinum resistant disease. 158 cases were retrospectively collected that received NACT between April 2013 and February 2018 at a single institution. The 3-tier Böhm CRS system was applied to the omentum and adnexa. Survival outcomes between scored subgroups were analyzed using Cox proportional hazards regression. Spearman rank correlation analyses were used to assess CRS and clinical data. 119 cases were treated only with Carboplatinum/Paclitaxel. Omental CRS was: 1 (23 cases, 19.3%), 2 (65 cases, 54.6%), and 3 (31 cases, 26.1%), while adnexal CRS was: 1 (50 cases, 42%), 2 (48 cases, 40.3%) and 3 (21 cases, 17.6%). The omental CRS was significantly associated with PFS as a 2-tier score (HR 0.612, 95% CI 0.378-0.989, p=0.045) but not associated with the PFS using the 3-tier score or with OS using either system. Adnexal CRS was not associated with OS but was significantly associated with PFS using the 3-tier (HR 0.49, 95% CI 0.263-0.914, p=0.025) and 2-tier scores (HR 0.535, 95% CI 0.297-0.963, p=0.037). The combined score was not associated with OS but was significantly associated with PFS using the 3-tier (HR 0.348, 95%CI 0.137-0.88, p=0.026) and 2-tier scores (HR 0.364, 95% CI 0.148-0.896, p=0.028). No CRS system used associated with laparoscopic assessment of disease. CRS in the omentum had no significant association with platinum resistance; however, the adnexal CRS 1/2 were three times as likely to develop platinum resistance compared to CRS 3 (RR 3.94, CI 1.03-15.09, p=0.046). The CRS, when used on the omentum, adnexa, and as a combined score, was significantly associated with PFS but not with OS. Adnexal CRS 1/2 are more likely to develop platinum resistant disease. Therefore, the use of this pathology parameter may be useful for clinical management.